Karl Barth and comparative theology - Moore-Keish, Martha L.; Collins Winn, Christian T. (Comparative theology--thinking across traditions., 2019)
This volume builds on recent engagements with Barth in theologies of religion, and opens new conversation between Barth and comparative theology. In each of six religion-specific sections, two theologians offer focused engagements of Barth with themes and figures from another religious tradition, followed by response from a theologian from that tradition itself.